The Influence of Brand Image and Price on Interest in Buying Toyota Cars at Auto 2000 Palembang City - Ummi Kalsum; Megawati Megawati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyze the effect of brand image and price on the intention to buy a Toyota car at Auto 2000 Palembang city. This study uses a descriptive quantitative method and a sample of 300 respondents. The data analysis method uses non-probability sampling, purposive sampling, and multiple regression using the SPSS version 26 test tool. Based on the research results, it shows that the Brand Image and Price variables have a significant and positive effect, both partially and simultaneously, on Interest in Buying Toyota Cars at Auto 2000 in the city of Palembang.